ELK1 Enhances Pancreatic Cancer Progression Via LGMN and Correlates with Poor Prognosis - Yan, Qiang; Ni, Chenming; Lin, Yingying; Sun, Xu; Shen, Zhenhua; Zhang, Minjie; Han, Shuwen; Shi, Jiemin; Mao, Jing; Yang, Zhe; Wang, Weilin (Frontiers in Molecular Biosciences, 2021)
Pancreatic cancer is one of the most lethal cancers and is associated with an extremely poor prognosis. Clarification of molecular mechanisms and identification of prognostic biomarkers are urgently needed. Though we previously found that LGMN is involved in pancreatic carcinoma progression, the upstream regulation of LGMN remains unknown. After searching for the transcription factors associated with the LGMN promoter, we identified ELK1 as a new regulator of LGMN transcription that binds directly to the LGMN promoter. More, ELK1 knockdown reduced pancreatic cancer cell proliferation, invasion and survival, while rescue with LGMN restored pancreatic cancer malignancy in vitro and in vivo. The overexpression of ELK1 further increased cancer cell proliferation, invasion and survival. Clinically, ELK1 and LGMN were positively correlated with clinical stage, differentiation and Lymphnode infiltration. ELK1 and LGMN were determined to be independent prognostic factors for overall survival. Patients with low ELK1/LGMN expression survived for a mean of 29.65 months, whereas those with high ELK1/LGMN expression have a mean of 16.67 months. Altogether, our results reveal a new mechanism by which ELK1 enhances pancreatic cancer progression via LGMN and correlates with a poor prognosis.